An Investigation On The Role Of Student Ethics And Data Privacy In The Implementation Of Educational Technology - Wang Ziheng; Nidhi Agarwal; Mohammad Nizamuddin Inamdar (Revista Electronica de Veterinaria, 2024)
This research, therefore, explores in intricate detail how an increase in new technologies through educational technology raises the questions of students' right to privacy and academic integrity. In short, data security and issues of ethical conduct among students have become significant concerns following the increasing use of digital technologies in schools as a means of enhancing learning experiences. This paper attempts to answer the question of how much students value data privacy by investigating the students' perceptions of ethical behavior and how this influences their acceptance of technology. The study aims to identify significant factors influencing students' and instructors' ethical choices in digital environments based on the administration of quantitative surveys and qualitative interviews. The results imply that ignorance of data privacy rights may lead to careless actions as it may compromise personal and institutional data. According to the study authors, such technology courses require integrating ethical education along these lines to promote accountability and confidence. Hopefully, our study can educate policymakers, teachers, and developers of technology about the need to promote proper data protection procedures and high standards of ethics in educational institutions.